PENGARUH PENDIDIKAN KEWIRAUSAHAAN, MOTIVASI DAN LINGKUNGAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA PADA UNIVERSITAS DI KOTA DENPASAR - Mahayasa, I Gede Aryana; Sumadi, Ni Komang; Satriya, I Wayan Budi; Prihantini Devi, I Gusti Ayu Hari; Yuniari, Ni Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022DO - 10.24843/EEB.2022.v11.i05.p06, 2022)
The success of an individual to become an entrepreneur is highly dependent on the entrepreneurial interest that the individual has. The role of entrepreneurs is needed by a country because it also determines the success of national development. The purpose of the study was to determine the effect of entrepreneurship education, motivation and the environment on students' interest in entrepreneurship at universities in Denpasar City. This research is an associative study or research and is carried out on students who come from colleges equivalent to private universities in Denpasar City. The research population is students from six universities in the city of Denpasar, with a total of 225 students as respondents. Collecting data using a questionnaire distributed online. The method of data analysis is descriptive and inferential. The results or research findings are the positive and significant influence of entrepreneurship education on motivation and interest in entrepreneurship. The environment has no significant effect on motivation, but has a positive and significant effect on interest in entrepreneurship.